2021
DOI: 10.3390/recycling6030060
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Various Factors for Geopolymer 3D Printing of Construction Products in Factories and on Construction Sites

Abstract: The utilization of geopolymer 3D printing for construction products in recent years has been exceptionally substantial, owing to their low carbon dioxide emissions, high-performance properties such as durability, and good thermal and mechanical properties. This automated manufacturing process reduces the need for additional formworks, capital investments, and human resources. Geopolymer 3D printing development is emerging because of its advanced use in construction applications. However, high costs of the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Construction efficiency can be reached also through automated manufacturing processes, such as geopolymer 3D printing. The research in [10] proposed an economic evaluation of each principal stage of geopolymer 3D printing, from the extraction of raw materials to printing. The required time, cost, and quality of a 50 m 2 geopolymer 3D-printed house in Finland was investigated.…”
Section: Methods and Trends For Recyclingmentioning
confidence: 99%
“…Construction efficiency can be reached also through automated manufacturing processes, such as geopolymer 3D printing. The research in [10] proposed an economic evaluation of each principal stage of geopolymer 3D printing, from the extraction of raw materials to printing. The required time, cost, and quality of a 50 m 2 geopolymer 3D-printed house in Finland was investigated.…”
Section: Methods and Trends For Recyclingmentioning
confidence: 99%
“…Energy efficiency in AM is crucial for mitigating environmental impact, reducing carbon footprints, and promoting sustainable manufacturing practices [34]. By minimizing energy consumption and material waste, energy-efficient AM processes contribute to a more environmentally friendly and cost-effective approach to production [35].…”
Section: Industrial Outlookmentioning
confidence: 99%
“…Geopolymer concrete used to have a CO 2 emission that was almost 10% lower than comparable concrete with a 100% OPC binder [ 12 ]. A recent study evaluated the viability of employing industrial wastes for geopolymer 3D printing in factories and building sites to provide a deep understanding of the construction cost, time, and energy consumption [ 37 ]. The study revealed that the use of sustainable materials by dependable and inexpensive manufacturing procedures in the building sector cuts the construction time and lowers the energy demand by about 50% compared with traditional manufacturing techniques.…”
Section: Performance—sustainability Characteristicsmentioning
confidence: 99%
“…The cost of producing a 3D-printed house is around 32% lower than the cost of producing a building using OPC and traditional manufacturing methods. As a replacement for OPC concrete in the building sector, an AAB concrete makes a positive contribution toward reducing the CO 2 emissions and global warming [ 37 ].…”
Section: Performance—sustainability Characteristicsmentioning
confidence: 99%